'Porosome' discovered nearly 20 years ago provides molecular insights into the kiss‐and‐run mechanism of cell secretion. Issue 7 (28th May 2015) - Jena, Bhanu P.
Abstract Secretion is a fundamental cellular process in living organisms, from yeast to cells in humans. Since the 1950s, it was believed that secretory vesicles completely merged with the cell plasma membrane during secretion. While this may occur, the observation of partially empty vesicles in cells following secretion suggests the presence of an additional mechanism that allows partial discharge of intra‐vesicular contents during secretion. This proposed mechanism requires the involvement of a plasma membrane structure called 'porosome', which serves to prevent the collapse of secretory vesicles, and to transiently fuse with the plasma membrane (Kiss‐and‐run), expel a portion of its contents and disengage. Porosomes are cup‐shaped supramolecular lipoprotein structures at the cell plasma membrane ranging in size from 15 nm in neurons and astrocytes to 100–180 nm in endocrine and exocrine cells. Neuronal porosomes are composed of nearly 40 proteins. In comparison, the 120 nm nuclear pore complex is composed of >500 protein molecules. Elucidation of the porosome structure, its chemical composition and functional reconstitution into artificial lipid membrane, and the molecular assembly of membrane‐associated t‐SNARE and v‐SNARE proteins in a ring or rosette complex resulting in the establishment of membrane continuity to form a fusion pore at the porosome base, has been demonstrated. Additionally, the molecular mechanism of secretory vesicle swelling, and its requirement for intra‐vesicular content release during cell secretion has also been elucidated. Collectively, these observations provide a molecular understanding of cell secretion, resulting in a paradigm shift in our understanding of the secretory process.